A novel strategy for realizing high nitrogen doping in Fe3C-embedded nitrogen and phosphorus-co-doped porous carbon nanowires: efficient oxygen reduction reaction catalysis in acidic electrolytes. Issue 30 (15th July 2019) - Li, Mian; Liu, Yang; Han, Lina; Xiao, Jie; Zeng, Xiaoyuan; Zhang, Chengxu; Xu, Mingli; Dong, Peng; Zhang, Yingjie
Abstract : A novel methodology for powerfully boosting the N doping amounts (9.26 at%) in three-dimensional (3D) Fe3 C-embedded N and P-co-doped porous carbon hybrid nanowires ( i.e. Fe3 C@NP-PCFs) and promoting the ORR catalytic activity in acidic electrolyte. Abstract : The achievement of higher nitrogen doping density is a prospective approach to further boost the oxygen reduction reaction (ORR) catalytic efficiency of non-precious-metal catalysts under acidic conditions. In this study, we report a novel methodology for powerfully promoting the N doping amounts in three-dimensional (3D) Fe3 C-embedded N and P-co-doped porous carbon hybrid nanowires ( i.e. Fe3 C@NP-PCFs). Via pyrolysis of the 3D polyvinylpyrrolidone (PVP)-cyanamide-Fe(C2 H3 O2 )2 –H3 PO4 precursor networks woven by the electrospinning technology, the desired products were successfully synthesized. In the pyrolysis process, upon the activation of phosphoric acid, the surfaces of the 3D Fe3 C@NP-PCF networks in situ formed abundant micro/mesopores and high-density carbon edges/defects, which contributed towards the instantaneous doping of more N atoms (9.26 at%) into the carbon frameworks of Fe3 C@NP-PCFs. The resultant Fe3 C@NP-PCF catalyst displayed highest ORR activity, comparable to that of 20 wt% Pt/C in 0.1 M KOH. In particular, the Fe3 C@NP-PCF catalyst revealed excellent ORR activity with the onset potential and half-wave potential being just 10.1 mV and 27.7 mV more negative than those of 20 wt% Pt/C, respectively. Its limited diffusion current density was even much larger than that of 20 wt% Pt/C in 0.5 M H2 SO4 . The electrochemical measurement results show that the Fe3 C@NP-PCFs catalyst also possesses better durability and methanol tolerance than 20 wt% Pt/C in both acidic and alkaline electrolytes. The special 3D hierarchically porous structures of the Fe3 C@NP-PCF nanowires and the fairly high active site dispersion along their surfaces are responsible for the excellent ORR activity of this catalyst.